ANALISIS PELANGGARAN ETIKA PERIKLANAN STUDI KASUS IKLAN DI INSTAGRAM HANASUI VERSI SERUM NO.1 DI INDONESIA - Theofanny; Najwa Putri Hidayat; Sheril Audi Seafi; Yogi Hamboro Bekti; Daniel Handoko (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study analyzes advertising ethics violations in Hanasui’s Instagram advertisement, which claims its serum product as the “No.1 Serum in Indonesia” without adequate data substantiation. The digital era and the high penetration of social media have transformed the advertising landscape but have also opened up opportunities for practices that violate the Indonesian Advertising Ethics (EPI). This research uses a qualitative approach with content analysis and case study methods to examine Hanasui's Instagram advertisements. The analytical framework is based on EPI articles related to honesty, responsibility, and substantiation of advertising claims. The findings indicate that the superlative claim “No.1 Serum in Indonesia” violates fundamental EPI principles, particularly in the aspects of honesty and responsibility, due to the absence of clear supporting data or methodology. This violation not only misleads consumers but also creates unfair competitive advantages and risks eroding consumer trust in the local cosmetics industry. The study also reveals challenges in implementing EPI in the context of social media, where the unique characteristics of digital platforms require adaptations to the existing regulatory framework. Recommendations include strengthening EPI enforcement mechanisms for digital advertising, developing specific social media guidelines, enhancing coordination with digital platforms, and implementing a peer-review mechanism within the advertising industry. This research contributes to the literature on communication ethics and provides practical insights for regulators, advertising practitioners, and academics in addressing advertising ethics challenges in the digital era.